Context of Usage Injectable Contraception in 1 and 3 Months at the First Year with the Weght Gain of Acceptor - Ani Media Harumi; Dwi Wahyu Wulan S.; Devi Fadhilah Septiana Putri (Aloha International Journal of Health Advancement (AIJHA), 2019)
Injectable contraception consist of hormone progesteron which grouped by 2 kinds of 1 month and 3 months injectable. Oftenly, the problem of injectable contraception is weight gain rate. Based on preliminary study in RB Delta Mutiara at the last 2 years ago, 520 injectable contraception acceptor are obtained by 1 and 3 months at the first year. The aim of this study is to know the context of using injectable contraception in 1 and 3 months at the first year with the weight gain of acceptor. This study used cross sectional design. The subjects were 123 1 month injectable contraception acceptors and 123 3 month injectable contraception acceptors. Independent variable was injectable contraception in 1 and 3 months. Dependent variable was of weight gain at the first year. The data were taken from the medical record, then analyzed using Chi square test. According to Chi square test, p-value was 0.02 (